2018
DOI: 10.1088/1755-1315/108/4/042059
|View full text |Cite
|
Sign up to set email alerts
|

Toxic heavy metal contamination assessment and speciation in sugarcane soil

Abstract: Abstract. The increasing heavy metal pollution in the sugarcane soils along the Great Huanjiang River was caused by leakage and spills of Lead (Pb) and Zinc (Zn) tailing dams during a flood event. Copper (Cu), Zn, Pb, Cadmium (Cd), and Arsenic (As) concentrations of soil samples collected from 16 different sites along the Great Huanjiang River coast typical pollution area were analyzed by Inductive Coupled Plasma Mass Spectrometry (ICP-MS). The mean concentrations of Pb, Cd, Zn, Cu, and As in the sugarcane soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The contamination order of the studied heavy metals was Cd> Pb> Cr> Ni under both sugarcane monoculture and crop rotation systems. Wang et al, (2018) revealed that Pb, Cd, As, and Zn were the major metal pollutants in sugarcane soils along the Huanjiang River, and their concentrations in all soil samples were higher than the heavy metal background value for Guangxi, indicating that sugarcane soils were polluted severely. In addition, Pb and Cd posed the highest environmental risk and constant threat to the ecosystem and human health.…”
Section: Index Of Geo-accumulation (Igeo)mentioning
confidence: 94%
See 3 more Smart Citations
“…The contamination order of the studied heavy metals was Cd> Pb> Cr> Ni under both sugarcane monoculture and crop rotation systems. Wang et al, (2018) revealed that Pb, Cd, As, and Zn were the major metal pollutants in sugarcane soils along the Huanjiang River, and their concentrations in all soil samples were higher than the heavy metal background value for Guangxi, indicating that sugarcane soils were polluted severely. In addition, Pb and Cd posed the highest environmental risk and constant threat to the ecosystem and human health.…”
Section: Index Of Geo-accumulation (Igeo)mentioning
confidence: 94%
“…These results showed that Cd, Cr, Ni and Pb made a large contribution to pollution in the case of sugarcane monoculture fields compared to crop rotation fields. The single contamination factor (Cf i ) proposed by Hakanson was used to assess the enrichment of the investigated heavy metals in the soils and to measure the pollution levels of sugarcane monoculture fields (Wang et al, 2013, Wang et al, 2018Tang et al, 2020).…”
Section: Index Of Geo-accumulation (Igeo)mentioning
confidence: 99%
See 2 more Smart Citations
“…The quantification of metallic specie is important for product quality control, observing the inorganic composition assurance and the presence of toxic elements to humans [5]. These determinations are routinely performed by flame atomic absorption spectrometry (F AAS), [6][7][8][9], inductively coupled plasma mass spectrometry (ICP-MS) [10], electrothermal atomic absorption spectrometry ET AAS [2,4,11,12,13] and UV-Vis spectrophotometry [14,15]. However, the energy dispersive X-ray fluorescence spectrometry (EDXRF) has not been explored for determination of inorganic species in sugar cane spirit.…”
Section: Introductionmentioning
confidence: 99%